"Ungovernable Feelings and Passions": Common Sense Philosophy and Mental State Defences in Nineteenth Century Scotland. Issue 3 (September 2016) - Kennedy, Chloë
Abstract : During the nineteenth century, changing conceptions of mental disorder had profound implications for the way that criminal responsibility was conceived. As medical writers and practitioners increasingly drew attention to the complexities of insanity, the grounds on which mentally abnormal offenders could be excused began to seem unduly restrictive. By way of a contribution to our understanding of this development, this article examines how the growing disparity unfolded in Scotland. The author argues that the requirements of the insanity defence, as set out within judicial directions, reflect core facets of Scottish Common Sense philosophical thought, including Thomas Reid's view of human agency and understanding of 'common sense'. Building on this contention, the author suggests that Scottish Common Sense philosophy played an important role in the development of Scottish mental state defences more broadly, and can provide an original interpretation of the way the doctrines of provocation and diminished responsibility changed during this era.